Technology At Work : At the Building Site - Richard Spilsbury (Oxford, United Kingdom Capstone Global Library Ltd, 2008)
Series looks at machines and tools in a variety of workplaces, offering explanations of how common and complex technologies work in the real world.
Keywords: Industry Innovation and Infrastructure; Non Fiction -- Non Fiction